Razlike v pogostosti pojavljanja nekaterih spremenljivk igralne učinkovitosti med zmagovalci in poraženci ter ekipami, ki so igrale neodločeno na moških evropskih rokometnih prvenstvih med leti 2002 in 2012 - Šibila, Marko (Šport (Ljubljana), 2014)
Six handball European Championshops were analysed with the aim of identifying the match statistics which best discriminated between winning, drawing and losing teams. Most interesting playing performance indicators were selected from six consecutive Men's European Championships held in the period from year 2002 to year 2012. Data were colected on 284 matches. The SPSS software package was used for statistical data processing. The results showed that the winning teams at the European Championships perform fast game with a large number of attacks. At the same time the players are very effective by executing the shots. Despite the rapid game winners do not make a large number of technical errors. The winning teams have statistically significant higher number of assists than their opponents. In defense they blocked significantly more shots and steal significantly more balls. The winning teams also have a very efficient goalkeepers who, on average, save significantly more shots than their opponents.
Keywords: analiza igre; discriminant analysis; European Championships; evropska prvenstva; handball; igralna učinkovitost; losers; match analysis; neodločeni izzid; performance indicators; poraženci; razlike; rokomet; sport; šport; teams that have played a draw; winners; zmagovalci